(untitled) (Journal of Academic Research, 2025)
The research paper aimed to learn about women’s mental health, learn about women’s empowerment, and learn about women’s sustainable development. That is the importance of mental health as an inseparable part of public health, especially when talking about women’s mental health, because women are half of society and it is important to become healthy, they are mothers, sisters and wives, they participate in social activities, and are active partners in decision-making, development and empowerment. And it is important to raise the quality of life, and it includes mental health, the state of physical, mental, and social legality, that women go through the stages of life, which reach these stages of life have an effective effect on women, because in order to overcome what they go through, psychological pressures and disorders do not exist. From continuous training, and encouraging concepts related to societal psychological problems practiced by women to achieve sustainable development. There is increasing evidence that change in the mental health agenda does not only require improved access to services and good care, but also requires more attention and investment in addressing the basic social and economic realities of life that make up mental health. The body is where it cannot be seen, and the woman is the only one who feels it, and she needs to be calm and quiet so that her condition does not worsen, so it extends to psychological treatment. The concept of empowerment and empowerment is the basis for the advancement of women, as it enables women to make decisions and demand rights and services, and the concept of empowerment is closely related to the concept of self-realization or presence, and the strengthening of capacities for participation and free choice, or for short the concept of capacity building Sustainable development is an expression of development that is characterized by stability and has factors of continuity and continuity, and forms all the patterns of development that are part of economic, social, and cultural development. Sustainable development consists of three main elements: the economic element, the social element, and the environmental element. The researcher was informed about a number of sources and learned about a number of Libyan and Arabic studies related to women’s psychological health, their empowerment, roles and effects in sustainable development, and benefited from their experiences and recommendations.